PML hyposumoylation is responsible for the resistance of pancreatic cancer. Issue 11 (16th September 2019) - Swayden, Mirna; Alzeeb, George; Masoud, Rawand; Berthois, Yolande; Audebert, Stéphane; Camoin, Luc; Hannouche, Laurent; Vachon, Hortense; Gayet, Odile; Bigonnet, Martin; Roques, Julie; Silvy, Françoise; et al.
Abstract : The dismal prognosis of pancreatic ductal adenocarcinoma (PDAC) is mainly due to its rapidly acquired resistance to all conventional treatments. Despite drug‐specific mechanisms of resistance, none explains how these cells resist the stress induced by any kind of anticancer treatment. Activation of stress‐response pathways relies on the post‐translational modifications (PTMs) of involved proteins. Among all PTMs, those mediated by the ubiquitin family of proteins play a central role. Our aim was to identify alterations of ubiquitination, neddylation, and sumoylation associated with the multiresistant phenotype and demonstrate their implications in the survival of PDAC cells undergoing treatment. This approach pointed at an alteration of promyelocytic leukemia (PML) protein sumoylation associated with both gemcitabine and oxaliplatin resistance. We could show that this alteration of PML sumoylation is part of a general mechanism of drug resistance, which in addition involves the abnormal activation of NF‐αB and cAMP response element binding pathways. Importantly, using patient‐derived tumors and cell lines, we identified a correlation between the levels of PML expression and sumoylation and the sensitivity of tumors to anticancer treatments.—Swayden, M., Alzeeb, G., Masoud, R., Berthois, Y., Audebert, S., Camoin, L., Hannouche, L., Vachon, H., Gayet, O., Bigonnet, M., Roques, J., Silvy, F., Carrier, A., Dusetti, N., Iovanna, J. L., Soubeyran, P. PML hyposumoylation is responsible for the resistance of pancreatic cancer. FASEB J. 33, 12447–12463 (2019). www.fasebj.org